PENGARUH MOTIF PENGGUNAAN MEDIA LINE TODAY TERHADAP KEPUASAN PENGGUNA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Fitra Annisa; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
LINE TODAY is a feature provided by chat based social media, i.e. LINE. Feature LINE TODAY provides the latest information from a variety of categories. The information is delivered directly to the user via a personal chat notifications. In theory the Uses and Gratification audiences essentially using mass media based on certain motifs, where the media is considered trying to meet the needs of khalayaknya. The purpose of this study, i.e. to find out how big the influence of motive media use the LINE TODAY against user satisfaction on student, Faculty of social and political sciences of the University of Riau, where the audience is the research on college students by using the media LINE TODAY.The method used in this research is quantitative method of explanation , the data collection through questionnaires. The location of the research done in the environmental school of social and political sciences of the University of Riau. The number of samples in this research as much as 96 respondents. Withdrawal of samples using techniques unknown populations. To find out how big the influence both of these variables, the researchers used a simple linear regression analysis. For the processing of data is carried out using a questionnaire, the statistical program Product And Service Solution (SPSS) Windows version 23.Based on the results of a simple linear regression for this research, the regression coefficient values obtained in this study were Y = 2.860 + 0.917 with significance level of 0.0000 and smaller than α = 0.05. Whereas on the basis of test results obtained, the determination of 71.70%. That is, there is a strong influence among the motives of the use of the media LINE TODAY against user satisfaction on student, Faculty of social and political sciences of the University of Riau. While the rest of 28.30% are influenced by other indicators that are not included in this study, then it means that the Ha received Ho denied.Keywords: social media, LINE TODAY, motive, gratification, satisfaction